Dampak covid-19 terhadap implementasi pembelajaran di era digital 4.0 - Alwan, Muhammad (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2021)
AbstractThis article discusses the impact of Covid-19 on the implementation of learning in the digital 4.0 era. On the other hand, this research also explores the potential for the emergence of student skills in the digital-based learning process. For this purpose, the research was conducted using a literature review (library research). The theme of learning related to Covid-19 has recently become interesting to study through research. Several research results found that e-learning-based learning with application variants during the pandemic was not significant. Contrary to the nature of digital learning media which always attracts the attention of students in general. This is relevant to the developmental period of children who are interested in digital visual media. On the other hand, 21st century life and career skills have begun to be tried in learning during the Covid-19 period such as flexibility and adaptability in the learning process during the Covid-19 period so as to bring out various creativity and independence among students.